Expert Consensus on Full-Cycle Rehabilitation for Elderly Patients with Chronic Heart Failure - HE Jing; JIA Jie; CHEN Xin; DONG Anqin; DING Yipeng; LIAO Weijing; ZHENG Jiejiao; YU Binbing; CHEN Zuobing; FANG Yuan; YAO Liqing; ZHU Yiping; et al. (康复学报)
Heart failure (HF) represents a severe manifestation or critical stage in the spectrum of cardiac diseases. Chronic HF has a relatively high prevalence, posing significant physiological, psychological, and social challenges to patients despite optimal medical management. Evidence supports the efficacy of standardized rehabilitation programs in mitigating functional limitations and enhancing the quality of life for these patients. In response, the "Expert Consensus on Full-Cycle Rehabilitation for Elderly Patients with Chronic Heart Failure" has been developed to further standardize the academic guidance and clinical practices regarding diagnosis, assessment, and treatment of chronic HF in the elderly. This consensus document delineates a structured approach to the definition, etiology, classification, staging, and grading of chronic HF in the elderly. It outlines a full-cycle rehabilitation work model, encompassing management processes, assessment of functional impairments, rehabilitation evaluations and therapeutic interventions. The full cycle rehabilitation model emphasizes a holistic rehabilitation cycle that addresses the entire disease trajectory, involves all relevant stakeholders, integrates tiered diagnostic and treatment approaches, and is adaptable across various geographical settings. This consensus elaborates in detail on the characteristics of functional impairments in elderly patients with chronic HF (cardiac function, pulmonary function, motor function, cognitive function, mental function, pain, dysfunction of defecation and urination, sensory and cognitive dysfunction, etc.), as well as the rehabilitation assessment and treatment methods. It is proposed that based on the rehabilitation assessment, personalized programs should be developed according to the specific conditions of the patients, including aerobic exercise, resistance training, inspiratory muscle training, breathing training, cognitive function training, mental and psychological support, etc.